The role of cardiologists on the stroke unit. (6th December 2020) - Doehner, Wolfram; Leistner, David Manuel; Audebert, Heinrich J; Scheitz, Jan F
Abstract: Cardiologists need a better understanding of stroke and of cardiac implications in modern stroke management. Stroke is a leading disease in terms of mortality and disability in our society. Up to half of ischaemic strokes are directly related to cardiac and large artery diseases and cardiovascular risk factors are involved in most other strokes. Moreover, in an acute stroke direct central brain signals and a consecutive autonomic/vegetative imbalance may account for severe and life-threatening cardiovascular complications. The strong cerebro-cardiac link in acute stroke has recently been addressed as the stroke-heart syndrome that requires careful cardiovascular monitoring and immediate therapeutic measures. The regular involvement of cardiologic expertise in daily work on a stroke unit is therefore of high importance and a cornerstone of up-to-date comprehensive stroke care concepts. The main targets of the cardiologists' contribution to acute stroke care can be categorized in three main areas (i) diagnostics workup of stroke aetiology, (ii) treatment and prevention of complications, and (iii) secondary prevention and sub-acute workup of cardiovascular comorbidity. All three aspects are by themselves highly relevant to support optimal acute management and to improve the short-term and long-term outcomes of patients. In this article, an overview is provided on these main targets of cardiologists' contribution to acute stroke management.